Analisis Tingkat Kepuasan Mahasiswa Terhadap Kualitas Layanan Akademik di Fakultas Ekonomi dan Bisnis Islam IAIN Samarinda - Komariah, Kokom; Tikawati, Tikawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
This study aims to describe the analysis of the level of student satisfaction with service quality at the Faculty of Economics and Islamic Business, IAIN Samarinda. This research was conducted by distributing questionnaires to 120 students of class 2017 Islamic Economics Department, Faculty of Economics and Islamic Business, IAIN Smarinda, in order to obtain primary data, namely direct information from respondents about what they felt was satisfaction in getting services at the Department of Economics, FEBI IAIN Samarinda. The questionnaire in this study was taken randomly and divided into 5 aspects of customer satisfaction, namely tangible, reliability, responsibility, assurance, empathy and information system aspects. The findings in this evaluation study indicated that the tangible aspect was felt satisfied by the majority of students. Likewise, the aspects of reliability, responsibility, assurance, empathy, and information system were felt satisfied by the majority of students. Even so, there are several aspects of each variable that need to be improved because there are many students who feel dissatisfied and even dissatisfied with the services provided.